Electrode Degradation Study of Vertically Aligned Carbon Nanotubes on a 3D Integrated Current Collector. Issue 12 (23rd September 2015) - Schroeder, Marshall A.; Pearse, Alexander J.; Kozen, Alexander C.; Lee, Sang Bok; Rubloff, Gary W.; Noked, Malachi
Abstract : Assembling nanostructured materials into rationally designed mesoscale arrays for use as electrodes in electrochemical systems is anticipated to reveal new challenges, particularly concerning new synthesis modes, architecture-related performance limitations, and degradation mechanisms. In this work, we focus on characterizing the degradation of densely packed vertically aligned carbon nanotubes (VACNTs) grown directly on a metallic foam to form a self-supporting, hierarchically porous 3D electrode architecture with an integrated current collector. The degradation pathways of this electrode, observed with microscopy and semi in-situ XPS after cycling as a redox scaffold in aprotic Li—O2 and Li—S batteries, shed new light on important design, performance, and degradation considerations for integrated mesoscale electrode architectures.